Formulation of the Regulation of the Function and Role of the Notary in Electronic General Meetings of Shareholders - Merry Koesnadi; John Pieris; Aarce Tehupeiory (International Journal of Artificial Intelligence Research, 2022)
Legal politics in the era of technological development, makes the legal profession, especially notaries, have to keep up with the times. A notary in carrying out his position as a Notary utilizes technology to facilitate the implementation of that position. Notaries as public/state officials have the authority to make authentic deeds. Notaries in carrying out their profession are required to adapt and keep up with the times, the goal is to be able to face the challenges of global competition. As time goes by, of course Science and Technology (Science and Technology) continues to develop, so that there are facilities such as internet networks and electronic media that can be used for two-way communication and make it possible to see each other such as chat, teleconference and video-conference . GMS can also be held via teleconference, considering cost and time efficiency. Law of the Republic of Indonesia Number 40 of 2007 concerning Limited Liability Companies regulates things that can be done through teleconference media regulated in Article 77 Paragraph (1) of the PT Law so that it allows shareholders to hold GMS without having to meet in person and be in one place but can carried out by teleconference which allows shareholders to see each other and actively interact in meetings. The method used in this research is normative legal research which is carried out as an effort to obtain the necessary data related to the problem. The data used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. In addition, primary data is also used to support secondary data legal materials. Data analysis was carried out using qualitative juridical analysis methods. Fromthe results of the study can be obtained that the GMS held by teleconference is invalid because it violates the provisions in Article 16 paragraph (1) letter m UUJN which requires the physical presence of the parties in the process of preparing an authentic deed so that the power of proof of the deed under the hands as a result of an act committed not in accordance with Article 16 Paragraph (1) letter m. Notaries in this case have roles and functions related to cyber notaries. The deed of the GMS was made with a cyber notary and the signing is permissible and legal to do because in Article 77 of the PT Law it is very clear that it is regulated, especially the signature gets legal protection provided by the ITE Law but the Cyber notary has not been fully supported by legislation in Indonesia, although there is a possibility, it cannot be carried out because it is limited by other laws, so cyber notaries cannot be implemented legally in Indonesia. There is still a need for specific arrangements regarding cyber notaries in Indonesia.